Effectiveness of digital game-based learning in elementary education: A systematic literature review - Fauzia Hasanah; Sandi Budi Iriawan; Effy Mulyasari; Zsalzsa Puspa Alivia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to systematically synthesize empirical evidence on the effectiveness of Digital Game-Based Learning (DGBL) in elementary education, focusing on both academic achievement and affective learning outcomes. A systematic literature review was conducted following the PRISMA protocol to ensure methodological rigor and transparency. Peer-reviewed empirical articles published between 2021 and 2025 were retrieved from the Scopus database using pre-defined inclusion and exclusion criteria. The selection process involved identification, screening, eligibility assessment, and final inclusion stages, resulting in 20 eligible studies. Data were analyzed using thematic synthesis to identify recurring pedagogical patterns and trends in outcomes across studies. The validity of the review process was ensured through clearly defined selection criteria, consistent screening procedures, and cross-checking of extracted data. The findings reveal that effective DGBL implementation is strongly associated with pedagogical alignment, particularly the integration of explicit learning objectives into game mechanics, immediate and adaptive feedback, student-centered learning approaches, progressive scaffolding, and functional gamification elements. These features consistently contributed to improvements in students’ academic achievement, conceptual understanding, and learning retention. In the affective domain, learning motivation and student engagement emerged as the most prominently enhanced outcomes, followed by positive shifts in learning attitudes and self-efficacy. The most stable and consistent effects were observed in language-related subjects, upper elementary grades (Grades 4–6), and formal classroom settings. Overall, the findings indicate that DGBL's effectiveness depends more on instructional and pedagogical design than on technological complexity, highlighting the importance of pedagogically grounded game-based learning in elementary education.